Two new genera and two new species of eriophyoid mites (Acari: Eriophyoidea) from North Bengal, India - Chakrabarti, Samiran; Sur, Surajit; Roy, Sourav; Sarkar, Sanjay (Zootaxa, 2017)
Two new genera and two new species of eriophyoid mites viz., Propeaciota genusetosis n. gen. and n. sp. infesting Acer sp. (Aceraceae) and Spinaephyes alnus n. gen. and n. sp. infesting Alnus nepalensis D. Don (Betulaceae) are described in the tribe Tegonotini (Eriophyidae: Phyllocoptinae) from North Bengal, India. Aciota secundum Flechtmann et al.1995 is re-assigned (n. comb.) to Propeaciota. Relationships of the new genera with other eriophyoid genera are discussed.